Integration of erm(B)-containing elements through large chromosome fragment exchange in Clostridium difficile - Wasels, François (Mob Genet Elements, 2015)
In Clostridium difficile, erm(B) genes are located on mobile elements like Tn5398 and Tn6215. In previous studies, some of these elements were transferred by conjugation-like mechanisms, mobilized in trans by helper conjugative systems. In this study, we analyzed the genomes of several recipient strains that acquired either Tn5398 or Tn6215-like elements. We demonstrated that the integration of the transposons in the genome of the recipient cell was always due to homologous recombination events, involving exchange of large chromosomal segments. We did not observed transposon transfer to a C. difficile strain in presence of DNAse, suggesting that a possible transformation-like mechanism occurred in this recipient.